Non-stoichiometric carbon-coated LiFexPO4 as cathode materials for high-performance Li-ion batteries. Issue 53 (3rd July 2017) - Feng, Ying; Gu, Junjie; Yu, Feng; Lin, Chunfu; Zhang, Jinli; Nie, Ning; Li, Wei
Abstract : This work first discloses the evolution of lattice parameters of the non-stoichiometric lithium iron phosphate crystals. Abstract : A series of non-stoichiometric carbon-coated lithium iron phosphate (LiFe x PO4 /C) have been prepared by a solid-state reaction to study the variation of electrochemical performance at different x values. Characterized by XRD in conjunction with Rietveld refinement, Mössbauer, TEM, Raman, etc., it is indicated that the Li–O bond is elongated in the Fe-poor non-stoichiometric lithium iron phosphate with decreasing x value, while the content of Fe2 P and graphitization degree of carbon layer in LiFe x PO4 /C samples is associated with the ratio of x . The powder electronic conductivity increases from 8.33 × 10 −2 S cm −1 to 16.67 × 10 −2 S cm −1 as the x value decreases from 1.04 to 0.98, which is due to a suitable amount of Fe2 P and a superior graphitized carbon layer. Among different Fe/Li ratios, LiFe0.98 PO4 /C exhibits the highest rate capability of 163.5 mA h g −1 at 0.1C and 93.5 mA h g −1 at 20C, as well as the largest diffusion coefficient of 12.6 × 10 −14 cm 2 s −1 . It is illustrated that the synergy effect of elongated Li–O bonds, moderate Fe2 P and graphitized carbon layer results in the high performance of non-stoichiometric LiFe x PO4 /C.